PENINGKATAN KINERJA SOLAR CELL CNT-ZNO NANO MATERIAL (DYE-SENSITIZED SOLAR CELL) DENGAN AUTO SCANNING POSISI MATAHARI 3 DIMENSI - Wibowo, Andri; Deni, Glar Donia; Guntoro, Kasto Wijoyo Teguh; Suseno, Jatmiko Endro (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2013)
This study proposed a tool that can set the direction of the solar cells that will always follow a shift of the light source and always facing perpendicular to the sun using solar system auto scanning. Commercial DSSC was proposed using a synthetic dye that is kind of a ruthenium complex dye has reached 10% efficiency, but the availability and the price is expensive does not allow for the development of this research so that the research will be used ZnO with Dye N3 a more easily available and cheaper. To optimize the performance of the solar cell, material will be added CNT nano-materials on silicon. Prototype of dye-sensitized solar cell (DSSC) was made using materials ZnO and CNTs that can increase the power by 5.18%. Auto scanning was able to move in 3 dimensions to follow the direction of motion of the sun through the increase reached 7.5%. Electric control system was set up by detecting the maximum light intensity and adjusting the position of the direction of the solar cell, solar lighting by using microcontroller ATMEGA 32, light sensor and motor driver. This technology had been able to improve 14.73%.